Effect of surface contamination on re-osseointegration of dental implants surrounded by circumferential bone defects - Mohamed, Seif (Trinity College (Dublin, Ireland). School of Dental Science, 2009)
This study was designed to evaluate the effect of surface contamination on re-osseointegration of dental implants surrounded by circumferential bone defect and to compare osseointegration around Osseotite® implants (Biomet 3I, Palm Beach Gardens, USA ) with that around Nanotite implants ( Biomet 3I, Palm Beach Gardens, USA ) in beagle dogs. MATERIALS AND METHODS: Four adult beagle dogs and 16 dental implants, eight commercially pure titanium 3.25mm x 13mm Osseotite® implants ( Biomet 3I, Palm Beach Gardens, USA ) and eight commercially pure titanium 3.25 x 13mm Nanotite™ implants ( Biomet 31. Palm Beach Gardens, USA ) were used. The lower premolars (P1, P2. P3 and P4) were extracted. Following 3 months of healing, bucccal and lingual mucoperiosteal flaps were raised and 4 implants (Two Osseotite® and two Nanotite™) were partially inserted in the left side of the mandible in each dog. Following five weeks of healing period, the implants were removed from the left sides, decontaminated by tooth brush and saline and placed into freshly prepared sites to the full implant length on the right side of each mandible. The coronal 5 mm of each implant was surrounded by 1.0 mm circumferential bone defect. Following 12 weeks of healing period, the dogs were sacrificed and the mandibles on experimental sides were harvested. Hard tissue ground sections were prepared of biopsies taken at the end of the study and histometric measurements were obtained.
Keywords: Dental Surgery, D.Ch.Dent.; Ph.D. Trinity College Dublin